PENGELOLAAN PARTICIPATING INTEREST WILAYAH KERJA MIGAS OLEH BADAN USAHA MILIK DAERAH - Suhariyanto, Didik; Setiawan, Puguh Aji Hari; Ekoprasetyo, Antonius Bintarto; Nurmawati, Bernadete; Panda, Daniel (The Juris, 2024)
Regulation of natural resource management as a pillar of life that is rooted in the welfare and balance of society is a mandate that must be carried out in good faith and with responsibility. One form of this can be found in Regional Owned Enterprises (BUMD), which is one of the channels for managing state assets. The provisions contained in the Minister of Energy and Mineral Resources Regulation Number 37 of 2016 concerning 10% Participating Interest in Oil and Gas Working Areas allow regional governments to participate in management through delegation to BUMD or regional companies. The essence of this effort is to obtain profits that can increase regional income and the welfare of its people. This 10% Participating Interest Regulation, from the start, has succeeded in creating harmony between the rights and obligations between Cooperation Contract Contractors (KKKS) and BUMD. KKKS is responsible for offering 10% participatory interest to regions, as regulated in Minister of Energy and Mineral Resources Regulation Number 37 of 2016. If regions accept this offer through BUMD, they will obtain a maximum management right of 10% in accordance with the mandate stated in the Cooperation Contract between the Special Task Force for Upstream Oil and Gas Business Activities (SKK Migas) and KKKS. In this way, cooperation between regional governments (BUMD and KKKS) can become a firm foundation for managing natural resources in order to achieve shared prosperity.